Impact of Bt Brinjal Cultivation in the Market Value Chain in Five Districts of Bangladesh - Shelton, Anthony M.; Sarwer, Sayed H.; Hossain, Md. J.; Brookes, Graham; Paranjape, Vijay (Frontiers in Bioengineering and Biotechnology, 2020)
Eggplant (brinjal) is a popular vegetable that provides an important source of income for small, resource-poor Bangladeshi farmers. The biggest constraint to brinjal production is the eggplant fruit and shoot borer (EFSB). This study was conducted in 2019 in five districts in Bangladesh and examined the impacts of using genetically engineered, insect-resistant brinjal (Bt brinjal) on its value and marketing. Based on a survey of Bt and non-Bt farmers, results indicate that Bt brinjal provided an average of 19.6% higher yield and 21.7% higher revenue compared to non-Bt varieties. On a per tonne basis, the revenue benefit of using Bt brinjal was 1.7%, reflecting different levels of acceptability among trade buyers and consumers. Some were prepared to pay higher prices for Bt brinjal compared to non-Bt brinjal because the fruit was less damaged, while others paid a price discount because the Bt brinjal was not available in preferred local varieties. Labor use, expressed in 8-hour days, for harvesting, grading and packaging of Bt brinjal was 14% higher for Bt brinjal, reflecting the increased yields of Bt brinjal. 83.1% of Bt brinjal growers were satisfied with the yields obtained, and 80.6% were satisfied with the quality of fruit. This contrasts with non-Bt brinjal growers where 58.7% were satisfied with their yields and 28% indicated that a large portion of their fruit was infested, not a concern for Bt brinjal. Three-quarters of Bt brinjal growers planned to plant Bt brinjal next season because of the apparent benefits achieved of higher yields, revenue and fruit quality. Many also highlighted the benefits of reduced insecticides. Of the non-Bt growers, 39.6% had not heard of Bt brinjal. However, after hearing more about the impact of the technology, 71.4% of them indicated they planned to grow Bt brinjal next season. These findings suggest there are significant benefits of Bt brinjal and highlight the importance of making the technology available in more varieties that are suitable to local conditions and consumer preferences. Additional studies are warranted to corroborate these findings and explore in more detail the factors influencing decisions made by farmers and consumers regarding Bt brinjal.